Challenges of economic reforms : impact on labour and industrial relations / edited by B. P. Gupta - Guha, B. P. (ed.) (Delhi, 1997)
This is an attempt to analyse the varying view points of important functionaries representing Trade Unions, Management. Government and Academics on the reform measures initiated in 1991. Based on the deliberations in a National Seminar organised in April, 1993, an Executive Summary was brought out a month later. There were suggestions for undertaking a review of the impact of the corrective actions recommended by the Seminar after allowing 3-4 years time for the new procedural changes to go into the system. This will enhance the usefulness of the study. Accordingly, this volume has been designed with an 'Epilogue' at the end, confining, however, to the various aspects concerning Labour.
Keywords: Economic reforms